Therapeutic value of tafamidis in patients with wild-type transthyretin amyloidosis (ATTRwt) with cardiomyopathy based on cardiovascular magnetic resonance (CMR) imaging. (3rd October 2022) - Chamling, B; Bietenbeck, M; Korthals, D; Drakos, S; Vehof, V; Stalling, P; Weil, M; Meier, C; Yilmaz, A
Abstract: Background: Tafamidis was approved in Europe for the treatment of cardiomyopathy (CM) in patients with transthyretin amyloidosis (ATTR) in April 2020. So far, real-world data addressing the therapeutic value of tafamidis for the treatment of ATTR-CM are scarce. The purpose of this study was to carefully analyse the therapeutic benefit of tafamidis in patients with wild-type ATTR (ATTRwt) and CM (ATTRwt-CM) after one year of therapy based on serial multi-parametric cardiovascular magnetic resonance (CMR) imaging. Purpose: The purpose of this study was to carefully analyse the therapeutic benefit of tafamidis in patients with wild-type transthyretin amyloidosis (ATTRwt) and cardiomyopathy (ATTRwt-CM) after one year of therapy based on serial multi-parametric cardiovascular magnetic resonance (CMR) imaging. Methods: The present study comprised N=40 patients with ATTRwt-CM who underwent two serial multi-parametric CMR studies within a follow-up period of 12±3 months. Baseline (BL) clinical parameters, serum biomarkers and CMR findings were compared to follow-up (FU) values in patients with treated "with" tafamidis 61mg daily (n=20, group A) and those "without" tafamidis therapy (n=16, group B). CMR studies were performed on a 1.5-T system and comprised (amongst others) cine-imaging for assessment of cardiac anatomy and function including 3D longitudinal strain assessment. In addition, a modified Look-Locker inversion recovery (MOLLI) T1-mapping sequence was performed for measurement of pre- and post-contrast myocardial T1-values with additional calculation of extracellular volume fraction (ECV)-values. Results: While left ventricular ejection fraction (LV-EF), left ventricular mass index (LVMi), left ventricular wall thickness (LVWT), native T1- and ECV-values remained unchanged in the tafamidis group A, a slight reduction in LV-EF (p=0.003) as well as a subtle increase in LVMi (p=0.034), in LVWT (p=0.001), in native T1- (p=0.038) and ECV-values (p=0.017) were observed in the untreated group B. Serum NT-proBNP levels showed an overall increase in both groups, however, with the untreated group B showing a relatively higher increase compared to the treated group A. Assessment of NYHA class did not result in significant intra-group differences when BL were compared with FU, but a trend to improvement in the treated group A compared to a worsening trend in the untreated group B (Δp=0.005). Conclusion: Tafamidis does not improve cardiac phenotype in patients with ATTRwt-CM after one year of therapy. However, tafamidis seems to slow down cardiac disease progression in patients with ATTRwt-CM compared to those without tafamidis therapy based on multi-parametric CMR data already after one year of therapy. Funding Acknowledgement: Type of funding sources: None.